Kenosis sebagai Fondasi Spiritualitas Kristen:Signifikansi Filipi 2:5–11 di Era Modern - Pamarto, Ageng Asih (STT Pelita Dunia, 2025)
This article argues that kenosis is the theological ground of Christian spirituality and a practicable ethic for communities today. Using a qualitative expository approach to Philippians 2:5–11, the study integrates textual criticism, form analysis, narrative–rhetorical mapping, and intertextual engagement with Isaiah 45:23. Close attention to key lexemes (morphē, harpagmos, ekenōsen, hyperypsōsen, Kyrios) clarifies that Christ’s self-emptying is not loss of divinity but the sovereign refusal to exploit privilege. Findings show that the hymn’s movement from preexistence to servanthood, obedience unto death, exaltation, and universal confession provides both a christological confession and a normative communal pattern. The novelty lies in bridging rigorous exegesis with a constructive spirituality of kenosis that critiques individualism, consumerism, power-obsession, and digital self-curation while grounding servant leadership and ecclesial unity. The study concludes that practicing kenosis self-giving love ordered to God’s glory reframes power as service and forms a credible public witness for the church.